Electrocatalytic Activity of Immobilized Co(II) on Porous Graphene Aerogels - Bagheri, Samira; Ramimoghadam, D.; Mansouri, N.; Hamid, Sharifah Bee Abd (Chinese Chemical Society Taiwan, 2016)
The highly-porous graphene aerogel (GA) with BET surface area of 810 m2 g−1 and three-dimensional structure has been successfully fabricated using the hydrothermal technique. The modified glassy carbon electrode was then prepared by casting the graphene aerogel solution followed by immersing the GA/GCE in Co+2 solution. The results showed that graphene aerogels improved the adsorption ability of the Co (II) ions. The electrocatalysis of oxygen evolution reaction (OER) at the Co-GA modified glassy carbon elec- trode (Co-GA/GCE) has been investigated using linear sweep voltammetry (LSV) in alkaline solution. The OER was noticeably enhanced at Co-GA/GCE, representing a negative shift in the LSV curve at the Co-GA/GCE compared to that obtained at the bare GCE. The high electrocatalytic activity, good reproducibility and low cost of proposed electrode provides desired characteristics of a potential candi- date in the industrial water electrolysis process.